Analysis and identification of coumarins in different parts of Chimonanthus salicifolius and biosynthetic pathways prediction - Jiang, Yu; Ma, Xinhua; Xu, Mimi; Xie, Tinghui; Tong, Yingpeng (Frontiers in Plant Science, 2025)
IntroductionChimonanthus salicifolius is a medicine-food homology plant in China with a long application history and various metabolites. However, there is currently a lack of innovative research of analytical approaches on secondary metabolites and integrated study on the chemical compounds of different parts in C. salicifolius. It is highly necessary to develop a novel workflow for rapidly screening and identifing metabolites, which will support material basis research for subsequently exploring the applications in fields of food and pharmaceutics of C. salicifolius.MethodsAn approach combined identification of in-house library and feature based molecular networking (FBMN) with characteristic fragment ions and neutral losses was employed to analyze the secondary metabolites in the different parts of C. salicifolius, with discussion of the diagnostic ion and neutral loss in coumarins and cinnamic acids. And differences in metabolites of different parts of C. salicifolius was analyzed by PCA, PLS-DA and volcano plots.Results and discussionA total of 200 compounds were identified, of which 69.04% were automatically annotated using self-built R script, effectively accelerating the identification of target compounds, and significantly improving the efficiency of compound structure annotation. The biosynthetic pathway of coumarins was predicted on basis of the identified compounds. Subsequently, a remarkable distinction of metabolites was observed from the shells of seed, leaves and seeds compared to the roots and branches, followed by a relatively minor disparity from branches and roots through PCA analysis and PLS-DA analysis. It was revealed in the heatmap that coumarins, flavonoids, terpenoids, atty acids and cinnnamic aicds were abundant in the leaves of C. salicifolius, providing material basis for subsequent pharmacological research.